Genetic polymorphisms contribute to acute kidney injury after coronary artery bypass grafting - (:unkn) unknown (FORUM MULTIMEDIA PUBLISHING, LLC, 2007)
Background. Acute kidney injury is one of the most serious complications after cardiac surgery. Genetic polymorphisms are reported to be associated with postoperative renal impairment. The aim of this study was to investigate the relationship between selected gene polymorphisms and acute kidney injury after cardiac surgery. Methods. Two hundred forty-eight elective coronary artery bypass grafting procedure patients were enrolled in the study. Angiotensin-converting enzyme (ACE) II, ID, and DD, apolipoprotein E (APO E), and angiotensin II type 1 receptor (AGTR1) A1166C genotypes were detected by polymerase chain reaction. Plasma levels of ACE were analyzed by enzyme-linked immunosorbent assay. Acute kidney injury after cardiac surgery was graded according to the RIFLE ( risk, injury, failure, loss, and end-stage kidney disease) classification. Results. In our study, 21.8% of patients had acute renal impairment after cardiac surgery. Among the 54 patients with acute kidney injury, ACE D allele frequency was 0.620. The plasma levels of ACE were significantly higher in the D allele carriers (P=.018). Three of the 54 patients with acute kidney injury were APO E epsilon 4 allele carriers (P=.002). AGTR1 C allele carriers constituted 46% of all patients with postoperative acute kidney injury. There was no statistically significant difference between A allele homozygotes and C allele carriers with respect to postoperative renal dysfunction (P >.05). Conclusions. The present findings support the hypothesis that ACE I/D and APO E gene polymorphisms may play a role in the development of acute kidney injury after cardiac surgery. However, AGTR1 does not have a unique association with postoperative renal impairment.
Keywords: ANGIOTENSIN-CONVERTING ENZYME; APOLIPOPROTEIN-E POLYMORPHISM; ACUTE-RENAL-FAILURE; INSERTION/DELETION POLYMORPHISM; DELETION POLYMORPHISM; CARDIAC-SURGERY; RISK; HEART; ASSOCIATION; MORBIDITY